Can We Target Endogenous Anti-inflammatory Responses as a Therapeutic Strategy for Inflammatory Bowel Disease? - Porter, Ross John (Inflamm Bowel Dis, 2018)
Inflammatory bowel disease (IBD) describes chronic relapsing remitting inflammation of the gastrointestinal tract including ulcerative colitis and Crohn’s disease. The prevalence of IBD is rising across the globe. Despite a growing therapeutic arsenal, current medical treatments are not universally effective, do not induce lasting remission in all, or are accompanied by short- and long-term adverse effects. Therefore, there is a clinical need for novel therapeutic strategies for IBD. Current treatments for IBD mainly manipulate the immune system for therapeutic gain by inhibiting pro-inflammatory activity. There is a robust endogenous immunoregulatory capacity within the repertoire of both innate and adaptive immune responses. An alternative treatment strategy for IBD is to hijack and bolster this endogenous capability for therapeutic gain. This review explores this hypothesis and presents current evidence for this therapeutic direction in immune cell function, cytokine biology, and alternative mechanisms of immunoregulation such as microRNA, oligonucleotides, and the endocannabinoid system.